Inhibition of auxin-induced ethylene production in cucumber fruit discs by carbon dioxide - Mathooko, Francis, M; Kubo, Yasutaka; Inaba, Akitsugu; Nakamura, Reinosuke (Elsevier B.V., 2003)
The induction of ethylene biosynthesis by indole-3-acetic acid (IAA) and its regulation by CO2 was examined in cucumber (Cucumis sativus L., var. Sharp-1) fruit discs. Treatment of discs with IAA significantly stimulated ethylene production and the extent depended on IAA concentration upto 1 mM. The increase in IAA-induced ethylene production was accompanied by increase in the activities of 1-aminocyclopropane-1-carboxylic acid (ACC) synthase and ACC oxidase (also known as ethylene-forming enzyme) and a massive accumulation of ACC and 1-(malonylamino)cyclopropane-1-carboxylic acid (MACC). The induction of ethylene production by IAA was inhibited by treatment with CO2. The extent of inhibition was dependent upon the concentration of CO2. Carbon dioxide inhibited IAA-induced ethylene biosynthesis by suppressing ACC synthase and ACC oxidase activities. Additionally, CO2 inhibited ACC conjugation into MACC. The results indicate that inhibition of ethylene production by CO2 in cucumber fruit discs following IAA treatment is due to inhibition of both ACC synthesis and ACC oxidation.
Keywords: Cucumber; Cucumis sativus; CO2; Auxin; Ethylene